Effects of cattle browsing on Terminalia sericea-dominated woodlands in a semi-arid region of the Kalahari, Namibia - Katjiua, Mutjinde(Mutjinde Levi Joseph) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2006.